Extracorporeal cardiopulmonary resuscitation: a national study on the association between survival and biomarkers of hypoperfusion, inflammation, and organ failure. (3rd October 2022) - Gregers, E; Moerk, S R; Linde, L; Andreasen, J B; Smerup, M; Kjaergaard, J; Moeller-Soerensen, P H; Holmvang, L; Christensen, S; Terkelsen, C J; Moeller, J E; Lassen, J F; et al.
Abstract: Background: In refractory out-of-hospital cardiac arrest (OHCA) with prolonged whole-body ischemia, global tissue injury proceeds even after establishment of circulation with extracorporeal cardiopulmonary resuscitation (ECPR). Purpose: We aimed to investigate the role of biomarkers reflecting hypoperfusion, inflammation, and organ injury in prognostication of patients with refractory OHCA managed with ECPR. Methods: This nationwide retrospective study included 226 adults with refractory OHCA managed with ECPR in Denmark (2011–2020). Biomarkers at admission and consecutively two days after ECPR initiation were retrieved. Odds ratio (OR) of 90-day survival were assessed by logistic regression analyses. Cut-off values were calculated from area under the curve (AUC) via the Youden index. Results: Fifty-six patients (25%) survived to hospital discharge, all were still alive after 90-days and 91% had a favorable neurological status at discharge. Factors independently associated with 90-day survival were: male sex, shockable presenting rhythm, low flow time, platelets, pH, lactate, C-reactive protein, lactate dehydrogenase (LDH), alkaline phosphatase (ALP), and creatine kinase MB (CK-MB) level. Comparing the ability of standard predictive variables (age, sex, shockable presenting rhythm, witnessed arrest, and low flow time) and selected biomarkers (from multivariate analyses) in predicting 90-day survival, biomarkers day 2 after OHCA were significantly better than standard variables (AUC 0.79 vs. 0.56, p=0.01). Conclusion: Biomarkers of hypoperfusion (low lactate and high pH), inflammation (high platelets and CRP), and organ failure (low LDH, ALP, and CK-MB) were independently associated with 90-day survival. Biomarkers on day 2 after OHCA (d-dimer, ALP, and CK-MB) were more predictive of 90-day survival than standard predictive variables. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Odense University Hospital's and Rigshospitalet's Common Research Foundation